Gear Wear Monitoring based on Wavelet Packet Energy and Modulation Signal Bispectrum Sideband Estimator - Xinyu Wen; Ruiliang Zhang; Fengshou Gu; Pu Liu; Yandong Shi (Jixie chuandong)
In order to improve the analytical result and robustness of modulation signal bispectrum based sideband estimator （MSB-SE）， a method for extracting wear characteristics combining wavelet packet energy （WPE） and MSB-SE is proposed. Firstly， the wavelet packet transform is used to decompose the signal into multiple frequency bands， and the WPE of each frequency band is calculated. The frequency band with higher energy is selected for reconstruction to optimize the analysis frequency band and reduce the calculation amount. Then， the MSB-SE is carried out to extract the characteristics of tooth surface wear， and the online monitoring of tooth surface wear damage state is realized by using a reasonable index. Simulation and experimental results show that the proposed method is more robust， and can more accurately monitor tooth surface wear and evaluate the degree of wear damage.